Peranan Sungai Kampar dan Siak dalam Proses Migrasi Orang Minangkabau ke Semenanjung Malaya - Efrianto Efrianto (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2023)
The Kampar River and Siak River play significant roles in the migration process of the Minangkabau people to the Malay Peninsula region. Historically, these rivers have served as vital routes connecting the inland areas of Sumatra with the East Coast of Sumatra Island. However, over time, the importance of these rivers has been forgotten, and the regions along the riverbanks have become underdeveloped and neglected. This article aims to shed light on the role of the Kampar and Siak Rivers as migration paths for the Minangkabau people, tracing their journey from their place of origin to various destinations along the East Coast of Sumatra and even reaching the Malay Peninsula. To achieve the objective of this article, a historical method comprising heuristics, source criticism, interpretation, and historiography is employed. The initial stage involves conducting a literature study and employing an interactive model analysis of technical data to gather relevant information. Subsequently, the gathered data undergoes source criticism, interpretation, and historiography. The Kampar River, known as a trade route since the era of the Srivijaya kingdom, is exemplified by the discovery of the Muara Takus Temple. This historical evidence confirms that the area was once prosperous and bustling. Consequently, the Minangkabau people utilized this pathway as an entry point to migrate to other regions, particularly the Malay Peninsula area.